Assessment of medical morbidities in a rhesus monkey model of naturally occurring low sociality. Issue 7 (12th April 2021) - Myers, Adam K.; Talbot, Catherine F.; Del Rosso, Laura A.; Maness, Alyssa C.; Simmons, Sierra M. V.; Garner, Joseph P.; Capitanio, John P.; Parker, Karen J.
Abstract: People with autism spectrum disorder (ASD) exhibit a variety of medical morbidities at significantly higher rates than the general population. Using an established monkey model of naturally occurring low sociality, we investigated whether low‐social monkeys show an increased burden of medical morbidities compared to their high‐social counterparts. We systematically reviewed the medical records of N = 152 ( n = 73 low‐social; n = 79 high‐social) rhesus macaques ( Macaca mulatta ) to assess the number of traumatic injury, gastrointestinal, and inflammatory events, as well as the presence of rare medical conditions. Subjects' nonsocial scores, determined by the frequency they were observed in a nonsocial state (i.e., alone), and macaque Social Responsiveness Scale‐Revised (mSRS‐R) scores were also used to test whether individual differences in social functioning were related to medical morbidity burden. Medical morbidity type significantly differed by group, such that low‐social monkeys incurred higher rates of traumatic injury compared to high‐social monkeys. Nonsocial scores and mSRS‐R scores also significantly and positively predicted traumatic injury rates, indicating that monkeys with the greatest social impairment were most impacted on this health measure. These findings from low‐social monkeys are consistent with well‐documented evidence that people with ASD incur a greater number of traumatic injuries and receive more peer bullying than their neurotypical peers, and add to growing evidence for the face validity of this primate model. Lay Summary: People with autism exhibit multiple medical problems at higher rates than the general population. We conducted a comprehensive medical record review of monkeys that naturally exhibit differences in sociality and found that low‐social monkeys are more susceptible to traumatic injuries than high‐social monkeys. These results are consistent with reports that people with autism also incur greater traumatic injury and peer bullying and add to growing evidence for the validity of this monkey model.